Statistical Downscaling Based Correction of the HadGEM2 Family General Circulation Models: Rimac Basin, Peru - Astorayme, MA (2017)
We would like to thank the PUPC and CONCYTEC for the opportunity given to carry out this work within the management agreement N° 27-2015 - FONDECYT between these institutions. In addition, the authors thank to SENAMHI and especially to Alan Llacza.